Dampak Penggunaan Teknologi Informasi Terhadap Proses Audit - Muhammad Fauzi Ilmi; Siti Ayu Pramudita; Rifda Aliyatul Bilbina Achmadi; Sarah Putri Aurellia; Yuni Sukandani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The development of information technology (IT) has made fundamental changes to various elements of life, and the audit process is no exception. This study aims to explore the impact of IT use on the efficiency, effectiveness, and quality of the audit process. The use of audit software, data analytics, and information management systems has enabled auditors to access and review sizable amounts of data quickly and accurately. IT not only accelerates the audit process but also improves the quality and reliability of audit results by enabling more detailed and comprehensive audits. The results showed that IT provides various benefits in the audit process, such as the use of IT on the audit process and IT on the audit implementation. However, this study also found several obstacles faced by auditors, namely the risk of using IT. This study concludes that the development of information technology is very rapid. The development of information technology has a significant impact on the sustainability of the company. The impact that can be felt by companies due to the application of information technology is an increase in the efficiency and effectiveness of the company and an increase in the company's internal control so that it can help the company to obtain precise and relevant information and help the company to achieve its goals.